Cytogenetic studies of Brazilian pediatric myelodysplastic syndrome cases: challenges and difficulties in a large and emerging country - Velloso, E.D.R.P.; Chauffaille, M.L.; Peliçario, L.M.; Tanizawa, R.S.S.; Toledo, S.R.C.; Gaiolla, Rafael Dezen [UNESP]; Lopes, L.F. (Associação Brasileira de Divulgação Científica (ABRADIC), 2013)
Myelodysplastic syndromes (MDS) and juvenile myelomonocytic leukemia (JMML) are rare hematopoietic stem cell diseases affecting children. Cytogenetics plays an important role in the diagnosis of these diseases. We report here the experience of the Cytogenetic Subcommittee of the Brazilian Cooperative Group on Pediatric Myelodysplastic Syndromes (BCG-MDS-PED). We analyzed 168 cytogenetic studies performed in 23 different cytogenetic centers; 84 of these studies were performed in patients with confirmed MDS (primary MDS, secondary MDS, JMML, and acute myeloid leukemia/MDS+Down syndrome). Clonal abnormalities were found in 36.9% of the MDS cases and cytogenetic studies were important for the detection of constitutional diseases and for differential diagnosis with other myeloid neoplasms. These data show the importance of the Cooperative Group for continuing education in order to avoid a late or wrong diagnosis.
Keywords: Childhood myelodysplastic syndromes; Juvenile myelomonocytic leukemia; Cytogenetics; Karyotype; Diagnosis